The Influence of Facilities and Infrastructure Management and Student Discipline on the Quality of the Learning Environment for Public High School Students in Indonesia - Jamaluddin Majid; Agus Setiyawan (Westscience Press, 2025)
This study examines the influence of facility and infrastructure management and student discipline on the quality of the learning environment for public high school students in Indonesia. Using a quantitative approach, data were collected from 250 students via a structured questionnaire measured on a 5-point Likert scale. Data analysis was conducted using SPSS version 25, including descriptive statistics and multiple linear regression. The results indicate that both facility and infrastructure management (β = 0.435, p < 0.001) and student discipline (β = 0.389, p < 0.001) have a significant positive effect on the quality of the learning environment. The regression model explains 56% of the variance in the dependent variable. The findings suggest that well-maintained school facilities and disciplined student behavior are essential for creating a conducive learning environment, highlighting the need for holistic strategies by school administrators and policymakers.